2011
DOI: 10.21608/jacb.2011.57270
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Load and Mycotoxinogenesis of Some Egyptian Medicinal Plants

Abstract: This investigation was designed to evaluate the fungal load of five randomly selected plant samples. A total of 150 dry samples of Basil, Mint, Marjoram, Chamomile and Fennel were collected from some markets in Egypt. All samples were analyzed among moulds and yeasts, also the samples were analysis for mycotoxins status. Fungi were found in most of the collected samples. The highest count of moulds presents in Mint, Basil, Marjoram, Fennel, and Chamomile in descending order, respectively, while the highest cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…In another study of African traditional herbal medicines sold in South Africa (Tshwane-Pretoria and Cape Town), all 16 samples were not contaminated with aflatoxins [ 17 ]. A study in Italy found that all samples of medicinal plants, aromatic herbs and herbal infusions were not contaminated with aflatoxins [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study of African traditional herbal medicines sold in South Africa (Tshwane-Pretoria and Cape Town), all 16 samples were not contaminated with aflatoxins [ 17 ]. A study in Italy found that all samples of medicinal plants, aromatic herbs and herbal infusions were not contaminated with aflatoxins [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the control of mycotoxins is inadequately funded, and many African governments do not give priority to mycotoxin control in medicinal plants [ 18 ]. However, the occurrence of mycotoxins has been reported in South Africa [ 16 , 17 ]; Kenya [ 19 , 20 , 21 ]; Nigeria [ 22 , 23 , 24 , 25 ]; and Egypt [ 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%